Strategi Pengembangan Home Industry Serundeng Ubi Jalar Jajanan Aulia di Kabupaten Bungo (Studi Kasus Jajanan Aulia Serundeng Ubi Jalar) - Asnawati Is; Ari Triyadi; Fikriman Fikriman (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
Finding out the Home Industry Development Strategy for Serundeng Sweet Potato Snack in the Auliadi Bungo Regency is the study’s goal (Case Study of Snack Aulia Serundeng Sweet Potato). Snack Aulia, Simpang Bebeko Village, Bathin II Babeko District, Bungo Regency served as the site for this study. The study was carried out between 30 February and 25 June 2020. Aulia Snack Serundeng, a company in Bungo Regency, was the subject of the study, which employed direct research to collect responses from one demographic. Using SWOT analysis, a quantitative descriptive analysis method was employed to examine the data provided in this research. The findings demonstrated that Aulia’s Serundeng Snack in Bungo Regency’s business development strategy was to increase the value of investments made in the business operations, establish partnerships with numerous snack food producers, continuously improve the quality of employees, use capital to increase production quality to maintain competitiveness, and increase market share. Maintaining and enhancing product quality in marketplaces like contemporary markets can help you compete with similarly manufactured items. To grow market share and become more well-known, increase advertising and promotions, and Cooperate more closely with owners of food stores or small markets to ensure seamless manufacturing. Introducing new products and using social media to promote them.